Study on the New Ethical Horizons in Gestational Surrogacy - Loike, John D.; Fischbach, Ruth L. (Medical Research and Its Applications Vol. 3, 2024)
This chapter highlights new ethical horizons in gestational surrogacy and reviews the emerging scientific evidence to show how maternal-fetal cell exchange (microchimerism) may affect the future health of both surrogate and fetus/child. Gestational surrogacy has become an increasingly popular, viable, and global option for couples including those unable to conceive or carry a fetus to term gay/lesbian couples, and couples/women who want a genetically related child without undergoing pregnancy. Gestational surrogacy occurs when a woman allows a 4-7-day embryo that was not generated from her own egg to develop in her uterus. In this paper, we review emerging scientific evidence to show how maternal-fetal cell exchange (microchimerism) may affect the future health of both surrogate and fetus/child. In light of these findings, we propose that four aspects of gestational surrogacy be examined: (1) the medical health and psychological outcomes of maternal-fetal cell exchange in surrogacy, (2) surrogacy laws and contractual agreements between the various parties, (3) provisions of a more comprehensive genetic family history and genetic screening from all parties involved, and (4) appreciation of the ethical and social complexities of surrogacy. We support gestational surrogacy provided that there is comprehensive informed consent. To be comprehensive, consent should include our current understanding of microchimerism with respect to the medical, legal, genetic, and ethical elements of surrogacy. This study supports that in the case of gestational surrogacy, full informed consent is obtained. In order to be thorough, consent ought to take into account the present comprehension of microchimerism concerning the ethical, legal, medical, and genetic aspects of surrogacy.